The aspects of the doctrine about the rock as one of the factors of soil formation - ZLOBENKO, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The influence of the geological rocks on the process of the soil formation is examined and the development of the scientifique views on the problem is analized.